Comparative Investigation on Fretting Wear of Nickel-Based Superalloy Surfaces Induced by Mechanical Polishing and Grinding. Issue 2 (4th March 2023) - Miao, Qing; Kuang, Weijie; Ding, Wenfeng; Dai, Chenwei; Yin, Zhen
Abstract: The purpose of this study is to comparatively investigate the wear behavior of nickel-based superalloy surfaces induced by mechanical polishing and grinding using the contact fretting against YG6 cemented carbide balls. Experimental results indicate that the friction coefficient and wear volume of the ground surface of nickel-based superalloy are smaller by 7.3% and by 18% on average, respectively, than those of the polished one. Furthermore, the high fretting wear loss of polished nickel-based superalloy can be attributed to the wear recirculation process composed of the plastic deformation, oxidization wear, surface and subsurface micro crack, which eventually leads to the significant material peeling and fatigue delamination. However, the ground nickel-based superalloy presents mainly the abrasive wear and excellent fretting wear-resistance due to the high hardness induced by grinding and the completely continuous compacted debris layer with few cracks instead of the ground surface to contact with the counterpart ball. Obtained results are beneficial for deepening the understanding of degradation mechanism during fretting of the nickel-based superalloy surfaces prepared by mechanical grinding and polishing.